Implications of the Niche Partitioning and Coexistence of Two Resident Parasitoids for Drosophila suzukii Management in Non-Crop Areas - Buonocore Biancheri, María Josefina; Núñez-Campero, Segundo Ricardo; Suárez, Lorena del Carmen; Ponssa, Marcos Darío; Kirschbaum, Daniel Santiago; Garcia, Flávio Roberto Mello; Ovruski Alderete, Sergio Marcelo (MDPI, 2023)
Understanding the mechanisms associated with the coexistence of competing parasitoid species is critical in approaching any biological control strategy against the globally invasive pest spotted-wing drosophila (=SWD), Drosophila suzukii (Matsumura). This study assessed the coexistence of two resident pupal parasitoids, Trichopria anastrephae Lima and Pachycrepoideus vindemiae Rondani, in SWD-infested fruit, in disturbed wild vegetation areas of Tucumán, northwestern Argentina, based on niche segregation. Drosophilid puparia were collected between December/2016 and April/2017 from three different pupation microhabitats in fallen feral peach and guava. These microhabitats were “inside flesh (mesocarp)”, “outside flesh”, but associated with the fruit, and “soil”, i.e., puparia buried close to fruit. Saprophytic drosophilid puparia (=SD) belonging to the Drosophila melanogaster group and SWD were found in all tested microhabitats. SD predominated in both inside and outside flesh, whereas SWD in soil. Both parasitoids attacked SWD puparia. However, T. anastrephae emerged mainly from SD puparia primarily in the inside flesh, whereas P. vindemiae mostly foraged SWD puparia in less competitive microhabitats, such as in the soil or outside the flesh. Divergence in host choice and spatial patterns of same-resource preferences between both parasitoids may mediate their coexistence in non-crop environments. Given this scenario, both parasitoids have potential as SWD biocontrol agents.